Rabies Virus 31D Peptide-[P(VP-co-AA)] Conjugates: Synthesis, Characterization and Cytotoxicity Evaluation - Arayici, Pelin Pelit; Acar, Tayfun; Ucar, Burcu; Karahan, Mesut; Arslan, Belkis Atasever; Mustafaeva, Zeynep (WILEY-V C H VERLAG GMBH, 2019)
The prevention of rabies disease, which has been the subject of many pieces of researches since ancient times, has become possible by vaccination. Therefore, new generation vaccine systems should be developed to achieve more effective, accessible and reliable vaccines than conventional vaccines against this disease. In this study, modificated Rabies virus 31D antigenic peptide epitope was synthesized by microwave supported solid phase peptide synthesis method and the synthesized peptide was characterized. Bioconjugates of the antigenic peptide epitope with poly (N-Vinyl-2-pyrrolidone-co-acrylic acid) that a biocompatible polymer was synthesized synthetically were synthesized at different ratios in the presence of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide. Characterization of bioconjugates was performed with Gel Permeation Chromatography and ZetaSizer. Cytotoxicity test was carried out using ECV304 human epithelial cells to determine the biocompatibility of peptide, polymer and bioconjugates. It is thought that the produced biocompatible synthetic peptide-polymer based rabies vaccine systems will contribute greatly to the vaccination studies.
Keywords: Conjugation; Cytotoxicity; Polymeric Adjuvant; Rabies; SPPS; ANTIGENIC PEPTIDE; VACCINES; ACID; CHROMATOGRAPHY; NANOPARTICLES; Chemistry